2011
DOI: 10.1038/onc.2011.178
|View full text |Cite
|
Sign up to set email alerts
|

Opposite modifying effects of HR and NHEJ deficiency on cancer risk in Ptc1 heterozygous mouse cerebellum

Abstract: Heterozygous Patched1 (Ptc1 þ /À ) mice are prone to medulloblastoma (MB), and exposure of newborn mice to ionizing radiation dramatically increases the frequency and shortens the latency of MB. In Ptc1 þ /À mice, MB is characterized by loss of the normal remaining Ptc1 allele, suggesting that genome rearrangements may be key events in MB development. Recent evidence indicates that brain tumors may be linked to defects in DNA-damage repair processes, as various combinations of targeted deletions in genes contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 48 publications
0
10
3
Order By: Relevance
“…Despite the critical role of the HR system for embryonic development, attenuated HR by deletion of Rad54 also did not result in lethality in Ptc1 +/-mice, implying redundancy in function of proteins involved in HR; however, in previous work, by exposing double Rad54/Ptc1 mutants to 2 Gy, we detected significantly increased MB tumorigenesis, possibly through the generation of viable but genetically rearranged neural cell precursors due to repair of DNA lesions by error-prone mutagenic pathways [21]. An analogous increase was not seen here, likely due to the lower dose used and relative radioresistance of Rad54 -/-mice [23].…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…Despite the critical role of the HR system for embryonic development, attenuated HR by deletion of Rad54 also did not result in lethality in Ptc1 +/-mice, implying redundancy in function of proteins involved in HR; however, in previous work, by exposing double Rad54/Ptc1 mutants to 2 Gy, we detected significantly increased MB tumorigenesis, possibly through the generation of viable but genetically rearranged neural cell precursors due to repair of DNA lesions by error-prone mutagenic pathways [21]. An analogous increase was not seen here, likely due to the lower dose used and relative radioresistance of Rad54 -/-mice [23].…”
Section: Discussioncontrasting
confidence: 50%
“…Our previous work showed that neonatal irradiation dramatically increases the frequency of MB [19,20]. We also showed that combined loss of Ptc1 and Rad54 or of Ptc1 and Parp-1 increased radiation induced MB [21,22]. Here, we analyzed the effects of combined loss of Rad54 and Parp-1 in the Ptc1 mouse model of spontaneous and radiation-induced cancer, highlighting novel synthetic lethal interactions during development and tumorigenesis, and dissecting the underlying cellular and molecular mechanisms.…”
Section: Research Papermentioning
confidence: 92%
“…By contrast, Rad54 inactivation generates a very low increase (approximately 1 apoptotic cell/1000 cells) in apoptosis in the mouse developing cerebellum at postnatal day 1 [46] and here we show the absence of significant increase in apoptosis in the developing cortex of Rad54 −/− mice compared to WT controls. Rad54 inactivation does not totally abrogate HR [34].…”
Section: Discussioncontrasting
confidence: 39%
“…F1 mice of the desired genotypes (DNA-PKcs 1/2 /Ptc1 1/2 3 DNA-PKcs 1/2 /Ptc1 1/1 and Rad54 1/2 / Ptc1 1/2 3 Rad54 1/2 /Ptc1 1/1 ) were intercrossed to produce F2 populations. Genotyping of mice was performed as described previously [24].…”
Section: Animal Breedingmentioning
confidence: 99%